Two new species of Cardiodectes Wilson, 1917 (Copepoda: Siphonostomatoida: Pennellidae) from gobiid fishes (Actinopterygii: Perciformes) in the western Pacific Ocean - Uyeno, Daisuke (Zootaxa, 2013)
Two new species of the genus Cardiodectes Wilson, 1917 (Siphonostomatoida: Pennellidae) are described based on fe-males from gobiid fishes (Actinopterygii: Perciformes) in coastal waters of the Pacific Ocean. Both new species belong to the ‘rubosus’ group sharing a trunk without an abdomen. Cardiodectes bellwoodi n. sp. parasitizes Istigobius nigroo-cellatus (Günther) in Australian waters and differs from members of the ‘rubosus’ group by having a trunk length less than twice its width, and a pair of large anterior lobes with branched processes. Cardiodectes shini n. sp. is similar to C. asper Uyeno & Nagasawa but is distinguishable by the presence of a well-developed, bilobed process between the bases of the maxillae, and by the cephalothorax bearing only two pairs of lobes.